DIGITAL IMMIGRANTS AND DIGITAL DECEPTION: CONSUMING AND COMBATING FAKE NEWS ONLINE - L Shinde, Parinitha; M. R, Sathyaprakash (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The present-day digital media ecosystem is defined by the proliferation of fake news. Although the term has become popular recently, its incidence has been exponential, and its omnipresence in the global news media, undeniable. Digital immigrants occupy an important online demographic. They represent individuals who were born prior to internet services becoming ubiquitous. They are projected to be the primary internet users in India by 2025 Statista (2022). Due to the existence of filter bubbles and algorithmic judgement on social media platforms, users get limited perspectives that reiterate their existing ideologies Baptista & Gradim (2020). This study seeks to investigate how digital immigrants understand, encounter, and respond to fake news. By conducting in-depth interviews with Indian digital immigrants, it was found that selective exposure was a predominant reason for fake news to be consumed. Confirmation bias explained why users sought out and remembered information which reinforced their ideas and attitudes, and muted and blocked sources which contradicted them. It is suggested that digital immigrants make concerted efforts such as exploring diverse points of views, undertaking basic training courses in fact-checking and source corroboration, and exhibiting cautiousness when encountering content in order to combat fake news.